THE ROLE OF NATIONALITY IN EDUCATION OF FUTURE MUSIC TEACHERS - E. Qobilova (Journals Park Publishing, 2025)
The content of this article focuses on the study of experiences in providing future specialists with theoretical and practical knowledge of Uzbek classical music, including maqoms, in educational institutions operating at various stages of the continuing education system. Analytical considerations are made on the specific aspects of musical education.
Keywords: Music, musical education, status, classical singing, traditional singing, research, education, mourning, music, decoration, spiritual and moral quality, music culture.